Fundamentals of neutrino physics and astrophysics - Giunti, Carlo (Oxford University Press, 2007)
This book deals with neutrino physics and astrophysics- a field in which some of the most exciting recent developments in particle physics, astrophysics and cosmology took place. The book is the most up-to-date, comprehensive and self-contained treatment of key issues in neutrino physics. It discusses all the topics vital to the understanding of the nature of neutrinos such as what they are, how to describe them, how they behave in nature, and the roles of neutrinos play in shaping our Universe.